2006
DOI: 10.1634/stemcells.2004-0159
|View full text |Cite
|
Sign up to set email alerts
|

Lamin A/C Expression Is a Marker of Mouse and Human Embryonic Stem Cell Differentiation

Abstract: Nuclear lamins comprise the nuclear lamina, a scaffoldlike structure that lines the inner nuclear membrane. B-type lamins are present in almost all cell types, but A-type lamins are expressed predominantly in differentiated cells, suggesting a role in maintenance of the differentiated state. Previous studies have shown that lamin A/C is not expressed during mouse development before day 9, nor in undifferentiated mouse embryonic carcinoma cells. To further investigate the role of lamins in cell phenotype mainte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
168
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 319 publications
(190 citation statements)
references
References 57 publications
17
168
1
Order By: Relevance
“…1C). An empirically fit exponential yields an effective time constant of 2.7 days for differentiation-associated stiffening of the nucleus relative to the cell body; this timescale appears roughly consistent with global changes in nucleoprotein expression such as lamins in ESCs (7,17). The limiting ratio for L nuc /L cell (i.e., nuclear:cytoplasmic stiffness) of Ϸ0.15 is also consistent with past measurements of relative nuclear compliance for other differentiated cells (18).…”
Section: Results and Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…1C). An empirically fit exponential yields an effective time constant of 2.7 days for differentiation-associated stiffening of the nucleus relative to the cell body; this timescale appears roughly consistent with global changes in nucleoprotein expression such as lamins in ESCs (7,17). The limiting ratio for L nuc /L cell (i.e., nuclear:cytoplasmic stiffness) of Ϸ0.15 is also consistent with past measurements of relative nuclear compliance for other differentiated cells (18).…”
Section: Results and Analysissupporting
confidence: 80%
“…Stem cell nuclei are therefore said to be more plastic than fully differentiated cells (3). Major differences are indeed found in chromatin conformation (4,5), nuclear protein expression (6)(7)(8), and also DNA and histone modification (9). Differentiation further entails immobilization of some nucleoplasmic proteins and is said to functionally ''rigidify'' the genome, setting a relatively permanent preference for particular expression profiles (10,11).…”
mentioning
confidence: 99%
“…Mass spectrometry analysis of Nip1 immunoprecipitates identified new potential Nip1 partners, among them lamin A/C. Lamin A/C is not observed in undifferentiated or proliferative cells, but its expression is activated in neuronal lineages and cardiomyocytes differentiated from human embryonic stem cells and in all mature and nearly mature neurons (22,25,64,65). Previously, it has been shown that undifferentiated P19 pluripotent mouse embryonal carcinoma cells contain low steady-state levels of lamins A/C RNAs that begin to increase 48 h after treatment with retinoic acid (23,66).…”
Section: Discussionmentioning
confidence: 99%
“…The member of type V intermediate filaments, lamins, are involved in nuclear organization by forming structures intercalated between chromatin and the inner nuclear membrane, DNA replication, and transcription, which are related to cell differentiation (19 -21). The expression of A-type lamins (lamins A/C) is associated with differentiated tissue and was shown to be present in mature and nearly mature neurons of rat brain (22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…T-cells and B-cells express only lamins of type B. Undifferentiated human and mouse embryonic stem cells lack lamins A/C, but express lamins B1 and B2 [63]. B-type lamin is expressed throughout embryogenesis, whereas lamin A and lamin C are not expressed until the tissue differentiation stage of development [64].…”
Section: Discussionmentioning
confidence: 99%